Stepping up : how to accelerate your leadership potential - Wood, Sarah; O'Keeffe, Niamh (Pearson Education Limited : FT Publishing, 2018)
Stepping up could be about taking on your first leadership or management role. It could be about changing your career, or leaving employment to start up on your own. It could be about changing the way you run a team already under your management. Whatever your circumstances, you will face the same issues we all do: changing attitudes, changing technology and our fast-moving rollercoaster of a world. Stepping Up will inspire and equip you to understand and respond to that change and develop your ability to lead yourself and others through it.